1997
DOI: 10.1557/jmr.1997.0195
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser deposition and characterization of conductive RuO2 thin films

Abstract: RuO2 thin films have been produced on silicon-based substrates by in situ pulsed laser deposition for the first time. The electrical properties, the surface characteristics, the crystalline structure, and the film-substrate interface of deposited samples have been investigated by 4-probe resistance versus temperature technique, scanning electron microscopy, x-ray photoelectron spectroscopy, x-ray diffraction, and transmission electron microscopy, respectively. The films show good electrical properties. The RuO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Fig.8(b)shows the Ru 3p spectrum of the RuO 2 modified sample. The Ru 3p 1/2 and 3p 3/2 peaks occur, respectively, at 485.3 and 463.0 eV, which agree well with the Ru 3p binding energy values reported for thin-film RuO 229 and nanocrystalline RuO 2 , 30 confirming that the chemical state of Ru in the surface-modification layer is similar to that in RuO 2 . RuO 2 has been studied as a cathode materials for over four decades [31][32][33].…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Fig.8(b)shows the Ru 3p spectrum of the RuO 2 modified sample. The Ru 3p 1/2 and 3p 3/2 peaks occur, respectively, at 485.3 and 463.0 eV, which agree well with the Ru 3p binding energy values reported for thin-film RuO 229 and nanocrystalline RuO 2 , 30 confirming that the chemical state of Ru in the surface-modification layer is similar to that in RuO 2 . RuO 2 has been studied as a cathode materials for over four decades [31][32][33].…”
supporting
confidence: 84%
“…[31][32][33] The lithium insertion/extraction process in RuO 2 cathode is a topotactic twophase reaction involving rutile RuO 2 4 tetragonal intermediate 4 orthorhombic LiRuO 2 . 29 In the potential range used in this study (i.e., 2.0-4.8 V), all three phases, which are both electronically and ionically conductive, 32,33 can be formed. This indicates that the RuO 2 modification layer can serve as both fast electron transfer and fast lithium ion diffusion channels.…”
Section: X-ray Photoelectron Spectroscopic (Xps) Studiesmentioning
confidence: 95%
“…However, the Ru 3d 3/2 peak (286.8 eV) has a significantly lower binding energy than the expected value given in the literature (287.6 eV) [26] for RuO 3 . The spin-orbit splitting of the two main ruthenium peaks of the unheated glass sample is thus 4.2 eV, which is more comparable to the spin-orbit splitting of RuO 2 (4.1 eV) than of RuO 3 (4.9 eV) [27]. Furthermore, RuO 3 is known to be an unstable phase [22].…”
Section: Cvd Of Ruo 4 On Glass Samplesmentioning
confidence: 80%
“…X-ray photoelectron spectroscopy and cyclic voltammetry have both demonstrated that the two oxide phases contain Ru in mixed oxidation states (i.e. Ru(III) and (IV) in RuO 2 ÁÂH 2 O, and Ru(III), (IV), and (VI) in RuO 2 ) [14,17,[30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%